Composition and origin of PM2.5 in Mediterranean Countryside. (March 2019) - Atzei, D.; Fermo, P.; Vecchi, R.; Fantauzzi, M.; Comite, V.; Valli, G.; Cocco, F.; Rossi, A.
Abstract: In this work PM2.5 was collected during winter and summer in a Sardinian village (Gonnostramatza, Italy) highly affected by biomass burning emissions. A multi-technique approach was adopted for the complete PM chemical characterization. The bulk characterization was performed by IC (Ion Chromatography), HPAEC (High-Performance Anion-Exchange Chromatography), TOT (Thermal Optical Transmittance) and ED-XRF (Energy-Dispersive X-Ray Fluorescence) while XPS (X-ray Photoelectron Spectroscopy) was used for the surface characterization. Using levoglucosan as specific tracer of biomass burning emissions, the assessment of the impact of this source was carried out and it represent the major PM source at the investigate site during winter. In winter the average levoglucosan concentration is 2096 ± 324 ng/m 3 while during summer its concentration is negligible (18 ± 7 ng/m 3 ). Levoglucosan content in PM2.5 during winter is on average 13.7%; it is estimated that 65% of PM2.5 is due to wood burning. XPS has been exploited in this work aiming at highlighting possible differences between surface and bulk composition of PM2.5 . The surface of the particulate matter resulted enriched in carbon compared to the bulk. Among the components of XPS C1s signals recorded on the samples collected during winter, it was found that the signal at 286.5 eV, which is due to the presence of COH, reflects the bulk composition of levoglucosan. Graphical abstract: Image 1 Highlights: PM2.5 was collected at a village highly impacted by wood/biomass emissions. Winter and summer samples composition is investigated by a multi technique approach. Large amounts of levoglucosan, a well-known marker of combustion, are detected. PM2.5 surface is enriched in carbon with no evidences of aromatic compounds. The surface concentration of COH reflects the bulk composition of levoglucosan.